2013
DOI: 10.1002/brb3.126
|View full text |Cite
|
Sign up to set email alerts
|

Neuromagnetic activation following active and passive finger movements

Abstract: The detailed time courses of cortical activities and source localizations following passive finger movement were studied using whole-head magnetoencephalography (MEG). We recorded motor-related cortical magnetic fields following voluntary movement and somatosensory-evoked magnetic fields following passive movement (PM) in 13 volunteers. The most prominent movement-evoked magnetic field (MEF1) following active movement was obtained approximately 35.3 ± 8.4 msec after movement onset, and the equivalent current d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 81 publications
0
45
0
3
Order By: Relevance
“…Additionally, several studies reported that muscle afferent inputs also reach M1 (Lucier et al, 1975; Zarzecki et al, 1978). Multiple cortical imaging techniques, including magnetoencephalography, functional MRI and positron emission tomography, have shown that electrical stimulation without muscle contraction and mechanical tactile stimulation to the index finger predominantly activates S1 (Xiang et al, 1997; Terumitsu et al, 2009), whereas motor-point stimulation with contraction of the extensor indicis muscle or passive finger movement activates both M1 and S1 (Weiller et al, 1996; Xiang et al, 1997; Nelles et al, 1999; Radovanovic et al, 2002; Terumitsu et al, 2009; Onishi et al, 2011, 2013). These results provide evidence that different brain regions are activated by mixed nerve stimulation with muscle contraction and sensory nerve stimulation to the index finger without muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies reported that muscle afferent inputs also reach M1 (Lucier et al, 1975; Zarzecki et al, 1978). Multiple cortical imaging techniques, including magnetoencephalography, functional MRI and positron emission tomography, have shown that electrical stimulation without muscle contraction and mechanical tactile stimulation to the index finger predominantly activates S1 (Xiang et al, 1997; Terumitsu et al, 2009), whereas motor-point stimulation with contraction of the extensor indicis muscle or passive finger movement activates both M1 and S1 (Weiller et al, 1996; Xiang et al, 1997; Nelles et al, 1999; Radovanovic et al, 2002; Terumitsu et al, 2009; Onishi et al, 2011, 2013). These results provide evidence that different brain regions are activated by mixed nerve stimulation with muscle contraction and sensory nerve stimulation to the index finger without muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence suggests that afferent somatosensory inputs such as peripheral nerve electrical stimulation (PES), muscle tendon vibration and active and passive movements can induce changes in primary motor cortex (M1) excitability (Naito et al, 1999, 2002; Ridding et al, 2000; Kaelin-Lang et al, 2002; Macé et al, 2008; Miyaguchi et al, 2013; Onishi et al, 2013; Kotan et al, 2015). Somatosensory inputs play a major role in motor control at the cortical level; this is a critical aspect of sensorimotor integration.…”
Section: Introductionmentioning
confidence: 99%
“…by an investigator moving the subject's finger or hand inside the magnetically shielding room (Druschky et al, 2003;Muthukumaraswamy, 2010;Onishi et al, 2013;Piitulainen et al, 2013a;Woldag et al, 2003;Xiang et al, 1997aXiang et al, , 1997b or by devices relying on a pneumatic cylinder-lever system (Alary et al, 2002;Lange et al, 2001). Pneumatic cylinders can evoke rapid intermittent passive movements, appropriate for example to measurements of passive-movement-evoked fields (pMEFs).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, passive finger movements elicited prominent responses in the contralateral sensorimotor cortex in accordance with earlier findings (Xiang et al ., ; Lange et al ., ; Alary et al ., ; Druschky et al ., ; Woldag et al ., ; Onishi et al ., ; Piitulainen et al ., , ). The corresponding cortical sources peaked ~ 70 ms after extension and ~ 90 ms after flexion movements.…”
Section: Discussionmentioning
confidence: 99%